Renal Ciliopathies: Sorting Out Therapeutic Approaches for Nephronophthisis - Stokman, Marijn F.; Saunier, Sophie; Benmerah, Alexandre (Frontiers in Cell and Developmental Biology, 2021)
Nephronophthisis (NPH) is an autosomal recessive ciliopathy and a major cause of end-stage renal disease in children. The main forms, juvenile and adult NPH, are characterized by tubulointerstitial fibrosis whereas the infantile form is more severe and characterized by cysts. NPH is caused by mutations in over 20 different genes, most of which encode components of the primary cilium, an organelle in which important cellular signaling pathways converge. Ciliary signal transduction plays a critical role in kidney development and tissue homeostasis, and disruption of ciliary signaling has been associated with cyst formation, epithelial cell dedifferentiation and kidney function decline. Drugs have been identified that target specific signaling pathways (for example cAMP/PKA, Hedgehog and mTOR pathways) and rescue NPH phenotypes in in vitro and/or in vivo models. Despite identification of numerous candidate drugs in rodent models, there has been a lack of clinical trials and there is currently no therapy that halts disease progression in NPH patients. This review covers the most important findings of therapeutic approaches in NPH model systems to date, including hypothesis-driven therapies and untargeted drug screens, approached from the pathophysiology of NPH. Importantly, most animal models used in these studies represent the cystic infantile form of NPH, which is less prevalent than the juvenile form. It appears therefore important to develop new models relevant for juvenile/adult NPH. Alternative non-orthologous animal models and developments in patient-based in vitro model systems are discussed, as well as future directions in personalized therapy for NPH.